Antiviral amide derivatives from Uvaria siamensis - Bastien Petit; Thibaud Goupil; Linh Hoang Phan; Charline Herrscher; Thomas Gaslonde; Xavier Cachet; Van Cuong Pham; Thi Mai Huong Doan; Karin Séron; Fanny Roussi; Sandy Desrat; Marc Litaudon; et al. (Phytochemistry, 2026)

Enhancing lipid accumulation in marine microalgae for sustainable biofuel applications: A review of Nannochloropsis and Tetraselmis - Linh Doan; Anh Q.V. Tran; Quynh K.L. Ong; Khanh G. Huynh; Khoa Tran; Thanh Khoa Phung (Biomass and Bioenergy, 2026)

A high-resolution record of early rift development and tectonic, sedimentary and environmental conditions in an active rift basin: IODP MSP drilling in the Corinth Rift, Greece (Expedition 381) - Lisa C. McNeill; Donna J. Shillington; Jeanine Ash; Gareth D.O. Carter; Richard E.Ll. Collier; Aleksandra Cvetkoska; Paula Diz; Mai-Linh Doan; Jeremy D. Everest; Natacha Fabregas; Eugenia Fatourou; Mary Ford; et al. (Marine Geology, 2026)

Effectively enhancing Pt-Ni nanocatalyst durability for ammonia oxidation toward efficient hydrogen production via polymer sacrificial protective layer and synergistic thermal engineering - Ta Nam Nguyen; Tuan Linh Doan; Huiseok Hong; Taekeun Kim (Fuel, 2026)

Synthesis, characterization, and ethanol vapor sensing characteristics of vanadium-based-MOFs with and without Cu doping - Tan Le Hoang Doan; Tae-Un Kim; Yujin Kim; My Van Nguyen; Ali Mirzaei; Ngoc Xuan Dat Mai; Linh Ho Thuy Nguyen; Hanh-Vy Tran Nguyen; Ha-Van Nguyen; Nhat Minh Quang Tran; Thang Bach Phan; Hyoun Woo Kim; et al. (Chemical Engineering Journal, 2026)

Partial replacement of soybean meal with fermented corn husk enhances growth, digestive enzymes, immune response, and growth-, immune-, and antioxidant-related gene expression in Nile tilapia (Oreochromis niloticus) reared in biofloc system - Hien Van Doan; Supreya Wannavijit; Khambou Tayyamath; Tran Thi Diem Quynh; Md Afsar Ahmed Sumon; Nguyen Vu Linh; Phisit Seesuriyachan; Yuthana Phimolsiripol; Maria Ángeles Esteban; Enric Gisbert (Aquaculture, 2026)

Effect of fermented corn cob (Zea mays L.) on growth performance, immunological response, and expression of immune-antioxidant genes in koi carp (Cyprinus carpio var. koi) reared in a low water exchange rearing system - Nguyen Vu Linh; Luu Tang Phuc Khang; Nguyen Dinh-Hung; Suwanna Wisetkaeo; Supreya Wannavijit; Yuthana Phimolsiripol; Phisit Seesuriyachan; Papungkorn Sangsawad; Patima Permpoonpattana; Hien Van Doan (Veterinary Research Communications, 2025)

Potential risk of P loss in salt-affected acidic soils amended with biochar or compost - Doan Thi Truc Linh; Chau Minh Khoi; Soh Sugihara; Nguyen Thi Kim Phuong; Nguyen Van Sinh; Huynh Mach Tra My; Tran Ba Linh; Dang Duy Minh; Koki Toyota (Journal of Soil Science and Plant Nutrition, 2025)

Influence of rice straw mulching on soil available silicate and maize growth in paddy fields affected by saline intrusion in the Mekong River Delta, Vietnam - Huynh Mach Tra My; Chau Minh Khoi; Jason Condon; Edward G. Barrett-Lennard; Brooke Kaveney; Susan Orgill; Dang Duy Minh; Nguyen Thi Kim Phuong; Tran Duy Khanh; Cao Dinh An Giang; Tran Minh Tien; Doan Thi Truc Linh; et al. (Plant and Soil, 2025)
Background and aims In Vietnam, Si accumulator crops like rice and maize crops are commonly rotated, but rice straw is often removed for animal feed. This study assessed whether rice straw mulch could improve soil available Si and maize growth. Methods A field experiment was conducted over three years in two fields with different soil Si levels. Four rice straw mulch levels (0, 3.5, 7, and 10.5 t ha⁻ 1 ) were applied during the maize growing season (Feb–Apr), and repeated for three years. In the 3rd year, soil samples were analyzed for available Si (phosphate buffer extraction) and Si fractions (CaCl 2 -Si, acetic acid-Si, H 2 O 2 -Si, oxalate-Si, and NaOH-Si). Maize yield and Si, N, P, K, and Na uptake were also evaluated. Results At the lower available Si field, rice straw mulch significantly increased the phosphate buffer-Si, CaCl 2 -Si and H 2 O 2 -Si in soil two weeks after sowing whereas the higher available Si field showed no differences among treatments. In contrast, the Si concentration in maize stems and leaves increased notably in the higher rice straw treatments at both sites. Furthermore, a negative correlation was found between Si and Na concentrations in the maize stems and leaves, suggesting that Si may play a role in mitigating Na uptake and reducing Na toxicity. Conclusion This study demonstrated that the application of 7 and 10.5 t ha⁻ 1 crop⁻ 1 of rice straw to fields with low available Si may enhance the soil Si availability, and improve Si, N, P, K uptake and tolerance to salt stress.

Dietary corn silk enhances growth, immunity, and gene expression in Nile tilapia (Oreochromis niloticus) cultured in a biofloc system - Hien Van Doan; Supriya Wannavijit; Khambou Tayyamath; Tran Thi Diem Quynh; Punika Ninyamasiri; Nguyen Vu Linh; Sang Van Vu; Phisit Seesuriyachan; Majid Khanzadeh; Seyed Hossein Hoseinifar (Fish & Shellfish Immunology, 2025)

Essential oil from Goniothalamus elegans Ast leaves in Vietnam: chemical composition, nitric oxide inhibition, and xanthine oxidase inhibition activities - Trang Huyen Xuan Hoang; Tuan Quoc Doan; Dien Dinh; Anh Tuan Le; Hoai Thi Nguyen; Linh Thuy Thi Tran (Natural Product Research, 2025)

Evaluation of the relative gene expression of FGF2, HAS2, BCL2, VEGFA, and PGR in repeat-breeder cows undergoing cyclicity or acyclicity - Punnawut Yama; Napatsorn Montha; Jakree Jitjumnong; Hien Van Doan; Nguyen Vu Linh; Warittha U-krit; Maslin Osathanunkul; Raktham Mektrirat; Julakorn Panatuk; Payungsuk Intawicha; Chien-Kai Wang; Tossapol Moonmanee (Reproductive Biology, 2025)

Influence of rice husk biochar pre-application on leachate quality and soil properties in green-manured clay loam Andosols - Nguyen Thi Kim PHUONG; Doan Thi Truc LINH; Koki TOYOTA; Nguyen Van SINH (Pedosphere, 2025)

Effects of fermented corn cob on growth performance, digestive enzyme, immune response, and gene expression of nile tilapia (Oreochromis niloticus) raised in biofloc system - Hien Van Doan; Supriya Wannavijit; Khambou Tayyamath; Tran Thi Diem Quynh; Punika Ninyamasiri; Nguyen Vu Linh; Sutee Wongmaneeprateep; Channarong Rodkhum; Phisit Seesuriyachan; Yuthana Phimolsiripol; Seyed Hossein Hoseinifar (Fish & Shellfish Immunology, 2025)

A novel plant-derived recombinant COBRA infectious bronchitis virus spike protein can elicit a strong immune response in chickens - Hang Thi Thu Hoang; Tra Thi Nguyen; Van Thi Pham; Tam Thanh Chu; My Thi Tra Le; Linh Nhat Doan; Hien Thi Thu Nguyen; Xuyen Thi Kim Le; Huong Thi Thanh Doan; Ha Hoang Chu; Ngoc Bich Pham (Veterinary Research Communications, 2025)

Porous transport electrodes for oxygen evolution reaction in proton exchange membrane water electrolysis -cells: Materials, designs, and diagnoses - Jaewoo Cho; Tuan Linh Doan; Sangjun Lee; In Gyeom Kim; Segeun Jang; Yuyan Shao; Taekeun Kim; Sehkyu Park (Chemical Engineering Journal, 2025)

Anesthetic Effects of Clove Basil Essential Oil (Ocimum gratissimum) Microemulsion on Asian Redtail Catfish (Hemibagrus wyckioides) and Its Biochemical Stress Indicators - Phuong Hong Lam; Huyen Da Nguyen Vo; Linh My Thi Truong; Dung My Thi Dang; Chien Mau Dang; Tin Chanh Duc Doan; Fatemeh Mollaamin; Majid Monajjemi (Fishes, 2025)
Ocimum gratissimum (clove basil) essential oil is known for its anesthetic and stress-reducing effects in aquatic animals. In this study, it was synthesized into a microemulsion form and its anesthetic effects on Hemibagrus wyckioides (Asian redtail catfish) juveniles were evaluated. The clove basil essential oil was formulated into a stable oil-in-water microemulsion with a particle size of approximately 36.3 nm and a polydispersity index (PDI) of 0.17. The microemulsion, with concentrations ranging from 125 mg L−1 to 250 mg L−1, effectively induced sedation and anesthesia in fish. It took approximately 2 to 4 min for the fish to reach a state of sedation or anesthesia, depending on the concentration of the clove basil essential oil microemulsion used. After a 30 min induction period using clove basil essential oil microemulsion at concentrations of 125 mg L−1 and 175 mg L−1, the blood cortisol, glucose, and lactate levels, which are stress indicators in fish, were evaluated. The results indicated that the blood cortisol levels in the treatments (6.97 to 7.4 μg dL−1) were consistently lower than in the control group (17.17 μg dL−1) throughout the induction time. However, the glucose (5.6–6.75 mmol L−1) and lactate levels (3.23–5.41 mmol L−1) in the treatment groups increased acutely during the induction time but returned to normal levels (around 3.5 mmol L−1 and 1.6 mmol L−1, respectively) during recovery. This contrasted with the control group, where the lactate and glucose levels remained slightly elevated during the recovery period. Additionally, the recovery time in fish anesthetized with clove basil essential oil microemulsion was consistently short across all of the treatments. These findings highlight the potential application of clove basil essential oil, particularly in microemulsion form, as an effective anesthetic agent for fish.

Two new flavonoids with antimicrobial activity from the roots of Byttneria aspera Colebr. ex Wall (Malvaceae) - Bich Ngan Truong; Thi Mai Huong Doan; Thuy Linh Nguyen; Van Nam Vu; Van Hieu Tran; Marc Litaudon; Van Cuong Pham (Natural Product Research, 2025)

Immunomodulatory and growth-promoting effects of supplementing red yeast (Sporidiobolus pararoseus) in fish meal-based diets for koi carp (Cyprinus carpio var. koi) cultured in a biofloc system - Nguyen Vu Linh; Supreya Wannavijit; Md Afsar Ahmed Sumon; Khambou Tayyamath; Nguyen Dinh-Hung; Christopher L. Brown; Thitikorn Nititanarapee; Patima Permpoonpattana; Wanaporn Tapingkae; Orranee Srinual; Hien Van Doan (Aquaculture International, 2025)

Effects of Mango Seed (Mangifera indica) Powder on Growth Performance, Immune Response, Gut Morphology, and Gene Expression of Nile Tilapia (Oreochromis niloticus) - Camilla Maria Fontana; Md Afsar Ahmed Sumon; Supreya Wannavijit; Anisa Rilla Lubis; Nuttapon Khongdee; Nguyen Vu Linh; Yuthana Phimolsiripol; Seyed Hossein Hoseinifar; Hien Van Doan (Fishes, 2024)
This study explored the effects of mango seed (MS) powder supplementation on the growth, immune response, gene expression, and intestinal morphology of Nile tilapia (Oreochromis niloticus) over an 8-week period. A total of 300 Nile tilapia fingerlings (average weight of 15.29 ± 0.05 g) were divided into five treatment groups and fed either a basal diet or one of four experimental diets containing MS powder at concentrations of 10 (MS10), 20 (MS20), 40 (MS40), and 80 (MS80) g kg−1. The results demonstrated that Nile tilapia fed MS-supplemented diets experienced significant improvements (p

Droplet digital PCR for fish pathogen detection and quantification: A systematic review and meta‐analysis - Md Afsar Ahmed Sumon; Edinson Dante Meregildo‐Rodriguez; Po‐Tsang Lee; Nguyen Dinh‐Hung; Earl T. Larson; Patima Permpoonpattana; Hien Van Doan; Won‐Kyo Jung; Nguyen Vu Linh (Journal of Fish Diseases, 2024)
This study provides a comprehensive summary of the findings regarding the application and diagnostic efficacy of droplet digital PCR (ddPCR) in detecting viral and bacterial pathogens in aquaculture. Utilizing a systematic search of four databases up to 6 November 2023, we identified studies where ddPCR was deployed for pathogen detection in aquaculture settings, adhering to Preferred Reporting Items for Systematic Reviews and Meta‐analysis of Diagnostic Test Accuracy guidelines. From the collected data, 16 studies retrieved, seven were included in a meta‐analysis, encompassing 1121 biological samples from various fish species. The detection limits reported ranged markedly from 0.07 to 34 copies/μL. A direct comparison of the diagnostic performance between ddPCR with quantitative PCR (qPCR) proved challenging due to limited data, thus only a pooled sensitivity analysis was feasible. The results showed a pooled sensitivity of 0.750 (95% confidence interval [CI]: 0.487–0.944) for ddPCR, compared to 0.461 (95% CI: 0.294–0.632) for qPCR, with no statistically significant difference in sensitivity between the two methods ( p = .5884). Notably, significant heterogeneity was observed among the studies ( I 2 = 93%–97%, p p p = .49). No publication bias was detected, and the studies generally exhibited a low risk of bias according to QUADAS‐C criteria. While ddPCR and qPCR showed comparable sensitivities in pathogen detection, ddPCR's capability to precisely quantify pathogens without the need for standard curves highlights its potential utility. This characteristic could significantly enhance the accuracy and reliability of pathogen detection in aquaculture.

Tuning the composition of highly stable mixed-metal MOFs by microwave-assisted hydrothermal method for ultra-high selective and simultaneous capture of CO2 and H2S - Manh B. Nguyen; Linh Ho Thuy Nguyen; Hoa Thi Lai; Huan V. Doan; Ngoc Quang Tran; Ngoc Xuan Dat Mai; Lam Dai Tran; Philip Anggo Krisbiantoro; Kevin C.-W. Wu; Tan Le Hoang Doan (Chemical Engineering Journal, 2024)

Multifunctional Microneedle Patch with Diphlorethohydroxycarmalol for Potential Wound Dressing - Tae-Hee Kim; Min-Sung Kim; Nam-Gyun Kim; Nguyen Vu Linh; Hien Van Doan; Young-Mog Kim; Sang-Hyug Park; Won-Kyo Jung (Tissue Engineering and Regenerative Medicine, 2024)

Acylphloroglucinol derivatives from the aerial parts of Syzygium borneense and their cytotoxic activities - Thi Van Nguyen; Thi Quynh Do; Marc Litaudon; Thuy Linh Nguyen; Van Nam Vu; Thu Huong Tran; Thi Mai Huong Doan; Van Cuong Pham (Phytochemistry Letters, 2024)

Influences of makiang (Syzygium nervosum) seed powder on growth performance, immunological response, antioxidant and immune related gene expression in juvenile Nile tilapia (Oreochromis niloticus) - Chinh Le Xuan; Nguyen Vu Linh; Supreya Wannavijit; Piyatida Outama; Camilla Maria Fontana; Puttinan Meepowpan; Hien Van Doan (Aquaculture, 2024)

Review of quorum‐quenching probiotics: A promising non‐antibiotic‐based strategy for sustainable aquaculture - Anisa Rilla Lubis; Md Afsar Ahmed Sumon; Nguyen Dinh‐Hung; Arun K. Dhar; Jérôme Delamare‐Deboutteville; Do‐Hyung Kim; Andrew P. Shinn; Duangkhaetita Kanjanasopa; Patima Permpoonpattana; Hien Van Doan; Nguyen Vu Linh; Christopher L. Brown (Journal of Fish Diseases, 2024)
The emergence of antibiotic‐resistant bacteria (ARBs) and genes (ARGs) in aquaculture underscores the urgent need for alternative veterinary strategies to combat antimicrobial resistance (AMR). These measures are vital to reduce the likelihood of entering a post‐antibiotic era. Identifying environmentally friendly biotechnological solutions to prevent and treat bacterial diseases is crucial for the sustainability of aquaculture and for minimizing the use of antimicrobials, especially antibiotics. The development of probiotics with quorum‐quenching (QQ) capabilities presents a promising non‐antibiotic strategy for sustainable aquaculture. Recent research has demonstrated the effectiveness of QQ probiotics (QQPs) against a range of significant fish pathogens in aquaculture. QQ disrupts microbial communication (quorum sensing, QS) by inhibiting the production, replication, and detection of signalling molecules, thereby reducing bacterial virulence factors. With their targeted anti‐virulence approach, QQPs have substantial promise as a potential alternative to antibiotics. The application of QQPs in aquaculture, however, is still in its early stages and requires additional research. Key challenges include determining the optimal dosage and treatment regimens, understanding the long‐term effects, and integrating QQPs with other disease control methods in diverse aquaculture systems. This review scrutinizes the current literature on antibiotic usage, AMR prevalence in aquaculture, QQ mechanisms and the application of QQPs as a sustainable alternative to antibiotics.

The influence of neighborhood dynamics on farmers’ intention to adopt e-commerce platforms for organic tea sales: a study in Thai Nguyen province of Northern Vietnam - Huy Quang Doan; Linh Truong Tuan; Nguyen Khanh Doanh (Organic Agriculture, 2024)

Black Soldier Fly (Hermetia illucens) Larvae Meal: A Sustainable Alternative to Fish Meal Proven to Promote Growth and Immunity in Koi Carp (Cyprinus carpio var. koi) - Nguyen Vu Linh; Supreya Wannavijit; Khambou Tayyamath; Nguyen Dinh-Hung; Thitikorn Nititanarapee; Md Afsar Ahmed Sumon; Orranee Srinual; Patima Permpoonpattana; Hien Doan; Christopher L. Brown (Fishes, 2024)
Insect meal has shown promise as a potentially sustainable source of nutrients for aquafeeds, offering an alternative to expensive and ecologically undesirable ingredients, in the context of population explosion and climate change. Despite this promising outlook, its effects on fish growth and immune responses remain to be thoroughly investigated. Our scientific goal was to experimentally test responses to replacements of the fish meal with a protein source derived from black soldier fly larvae meal (BSFLM). Possible impacts on growth, immunological response, and the expression of selected immune-system related genes were evaluated in Koi carp (Cyprinus carpio var. koi) using a biofloc culture system. Three hundred fish (20.0 ± 0.2 g) were allocated into five groups: a control group receiving a basal diet containing 0 g kg−1 BSFLM and four experimental groups in which fish meal was replaced with 50, 100, 150, and 200 g kg−1 BSFLM for eight weeks. After 4 weeks of feeding, there were no statistically significant differences in specific growth rate (SGR), feed conversion ratio (FCR), and survival rate between fish fed BSFLM-enriched diets at 50, 100, 150 g kg−1 and a control (0 g kg−1 BSFLM) diet. However, fish fed 200 g kg−1 BSFLM showed significantly improved weight gain (WG) and SGR compared to the control after 4 weeks; this difference persisted through 8 weeks (p

Effects of hyperoxia during oxygen nanobubble treatment on innate immunity, growth performance, gill histology, and gut microbiome in Nile tilapia, Oreochromis niloticus - Nguyen Vu Linh; Nareerat Khongcharoen; Dinh-Hung Nguyen; Le Thanh Dien; Naruporn Rungrueng; Chayuda Jhunkeaw; Pattiya Sangpo; Saengchan Senapin; Toungporn Uttarotai; Wattana Panphut; Sophie St-Hilaire; Hien Van Doan; et al. (Fish & Shellfish Immunology, 2023)

Corrigendum to “Coastal environmental changes in Southeast Asia: A study from Quang Nam Province, Central Vietnam” [Reg. Stud. Mar. Sci. 39 (2020) 101420] - Bijeesh Kozhikkodan Veettil; Juliana Costi; Wiliam Correa Marques; Xuan-Linh Tran; Ngo Xuan Quang; Dong Doan Van; Pham Ngoc Hoai (Regional Studies in Marine Science, 2023)

The first maternal genetic study of hunter-gatherers from Vietnam - Huyen Linh Tran; Huong Pham Mai; Dung Le Thi; Nhung Doan Thi; Lam Le Tung; Tung Pham Thanh; Ha Tran Manh; Hung Nguyen Mau; Hoang Ha Chu; Ha Hoang (Molecular Genetics and Genomics, 2023)

Phylogenotyping of infectious bursal disease virus in Vietnam according to the newly unified genotypic classification scheme - Xuyen Thi Kim Le; Roan Thi Do; Huong Thi Thanh Doan; Khue Thi Nguyen; Linh Thi Khanh Pham; Thanh Hoa Le (Archives of Virology, 2023)

New alkaloids from the stem bark of Cinnamomum bejolghota - Thi Phuong Le; Bich Ngan Truong; Marc Litaudon; Thuy Linh Nguyen; Thi Mai Huong Doan; Van Cuong Pham (Phytochemistry Letters, 2023)

Lasibidoupins A and B, two new compounds from the stems of Lasianthus bidoupensis V.S. Dang & Naiki - Nguyen Kim Tuyen Pham; Thi Diem Huong Nguyen; Thi Mong Cam Nguyen; Gia Dinh Nguyen; Cong Doan Huynh; Thi Nga Vo; Thi Quynh Trang Nguyen; Thuc Huy Duong; Van Son Dang; Bui Linh Chi Huynh; Thi Ngoc Mai Tran; Tan Phat Nguyen (Natural Product Research, 2023)

Insulin-mimetic activity of 23-glycosyl oleanane triterpenoids isolated from Gymnema latifolium - Ha-Thanh-Tung Pham; Eun-Jin Park; Byeol Ryu; Hee-Ju Lee; Thi-Phuong Doan; Hyo-Moon Cho; Thi-Linh-Giang Pham; Won-Keun Oh (Phytochemistry, 2023)

Biochar from Cyperus alternifolius Linn.: from a waste of phytoremediation processing to efficient depolluting agent - Linh T. T. Nguyen; Phuong T. Le; Tien A. Nguyen; Nhuan N. Doan; Kwangsoo No (Environmental Science and Pollution Research, 2023)

Efficacy of Different Routes of Formalin-Killed Vaccine Administration on Immunity and Disease Resistance of Nile Tilapia (Oreochromis niloticus) Challenged with Streptococcus agalactiae - Nguyen Vu Linh; Le Thanh Dien; Ha Thanh Dong; Nuttapon Khongdee; Seyed Hossein Hoseinifar; Mohamed Saiyad Musthafa; Mahmoud A. O. Dawood; Hien Van Doan (Fishes, 2022)
Vaccines prepared from formalin-killed Streptococcus agalactiae were administered to Nile tilapia (Oreochromis niloticus) via three different routes: immersion in a water-based vaccine, injection with an oil-based vaccine, and as a water-based oral vaccine. All vaccination treatments increased lysozyme and peroxidase activity in skin mucus of Nile tilapia by 1.2- to 1.5-fold compared to their activities in unvaccinated control fish. Likewise, alternative complement, phagocytosis, and respiratory burst activities in the blood serum of the vaccinated fish were 1.2- to 1.5-times higher than in the unvaccinated fish. In addition, the expression transcripts of interleukin-1 (IL-1), interleukin-8 (IL-8), and lipopolysaccharide-binding protein (LBP) were 2.3- to 2.9-fold higher in the vaccinated fish compared to those in the unvaccinated control. The unvaccinated fish challenged with Streptococcus agalactiae had a survival rate of 25% compared to a survival rate of 78–85% for the vaccinated fish. The differences between the unvaccinated and vaccinated fish were all statistically significant, but there was no significant difference in any of the indicators of immunity between the three vaccinated groups. Collectively, these results confirm that vaccination with formalin-killed Streptococcus agalactiae significantly improved the resistance of Nile tilapia to infection by the pathogen. Overall, the efficacy of oral administration of the vaccine was comparable to that of vaccine administered via injection, indicating that oral vaccination is a viable cost-effective alternative to administering vaccines by injection.

Molecular genotypic analysis of porcine circovirus type 2 reveals the predominance of PCV2d in Vietnam (2018–2020) and the association between PCV2h, the recombinant forms, and Vietnamese vaccines - Huong Thi Thanh Doan; Roan Thi Do; Pham Thi Phuong Thao; Xuyen Thi Kim Le; Khue Thi Nguyen; Nguyen Thi Thu Hien; Luu Minh Duc; Linh Thi Khanh Pham; Thanh Hoa Le (Archives of Virology, 2022)

Investigation of bioactive chemical constituents and anti-cancer activity of ethanol extract of Curcuma singularis Gagnep rhizomes - Chinh Chung Doan; Thanh Long Le; Nguyen Quynh Chi Ho; Thi Linh Giang Tran; Nguyen Tu Linh Le; Quang Dao Vu; Thi Hong Lan La; Viet Cuong Nguyen; Thi Phuong Thao Nguyen; Nghia Son Hoang (Natural Product Research, 2022)

Passionfruit (Passiflora edulis) Peel Powder Stimulates the Immune and Antioxidant Defense System in Nile Tilapia, Oreochromis niloticus, Cultivated in a Biofloc System - Piyatida Outama; Nguyen Vu Linh; Chinh Le Xuan; Supreya Wannavijit; Sudaporn Tongsiri; Chanagun Chitmanat; Napatsorn Montha; Hien Van Doan (Fishes, 2022)
This study aimed to assess the impacts of dietary supplementation with passionfruit (Passiflora edulis) peel powder (PSPP) on the growth, immune response, and expression of immune and antioxidant-related genes in Nile tilapia (Oreochromis niloticus) maintained in a biofloc system. Fish were fed basal diets supplemented with different doses of PSPP at 10 g kg−1 (PSPP10), 20 g kg−1 (PSPP20), 40 g kg−1 (PSPP40), and 80 g kg−1 (PSPP80). The basal diet, without PSPP-supplementation, was used as a control at 0 g kg−1 (PSPP0). We observed that the dietary supplementation groups fed different levels of PSPP exhibited no substantial difference or only slight increases in growth performance and immunological response in Nile tilapia (p > 0.05), whereas fish fed diets supplemented with PSPP at concentrations of 10 g kg−1, 20 g kg−1, and 40 g kg−1 had significantly higher mRNA transcripts (approximately 1.5–4.5 fold) of immune (il-1, il-8, and lbp) and antioxidant (gst-α, gpx, and gsr) gene expressions than fish in the control treatment group (0 g kg−1). These findings suggest that dietary supplementation with PSPP may effectively stimulate the immune and antioxidant defense system and may function as feed additives in Nile tilapia cultured in a biofloc system.

Zoning the suitability of the western Mekong Delta for paddy rice cultivation and aquaculture under current and future environmental conditions - Hue Doan Van; Xuan Ai Tien Thi; Van Linh Le Thi; Thanh To Van; Nhat Truong Pham; Nguyen Tan Phong; Alexandre S. Gagnon; Quoc Bao Pham; Duong Tran Anh (Environmental Monitoring and Assessment, 2022)

Loop-mediated isothermal amplification (LAMP) assay for detection of sesame phyllody phytoplasmas in Vietnam - Nguyen Bao Quoc; Nguyen Thi Thanh Xuan; Nguyen Mai Nghiep; Nguyen Doan Nguyen Phuong; Ton Bao Linh; Nguyen Ngoc Bao Chau; Nguyen Duc Xuan Chuong; Nguyen Chau Nien; Matthew Dickinson (Folia Microbiologica, 2021)

A novel approach for predicting daily pan evaporation in the coastal regions of Iran using support vector regression coupled with krill herd algorithm model - Yiqing Guan; Babak Mohammadi; Quoc Bao Pham; S. Adarsh; Khaled S. Balkhair; Khalil Ur Rahman; Nguyen Thi Thuy Linh; Doan Quang Tri (Theoretical and Applied Climatology, 2020)

Identification of EDI trend using Mann-Kendall and Şen-Innovative Trend methods (Uttarakhand, India) - Anurag Malik; Anil Kumar; Quoc Bao Pham; Senlin Zhu; Nguyen Thi Thuy Linh; Doan Quang Tri (Arabian Journal of Geosciences, 2020)

Developing Novel Robust Models to Improve the Accuracy of Daily Streamflow Modeling - Babak Mohammadi; Farshad Ahmadi; Saeid Mehdizadeh; Yiqing Guan; Quoc Bao Pham; Nguyen Thi Thuy Linh; Doan Quang Tri (Water Resources Management, 2020)

Potential of Hybrid Data-Intelligence Algorithms for Multi-Station Modelling of Rainfall - Quoc Bao Pham; S. I. Abba; Abdullahi Garba Usman; Nguyen Thi Thuy Linh; Vivek Gupta; Anurag Malik; Romulus Costache; Ngoc Duong Vo; Doan Quang Tri (Water Resources Management, 2019)

Microstructures Induced in Porous Limestone by Dynamic Loading, and Fracture Healing: An Experimental Approach - Julie Richard; Mai-Linh Doan; Jean-Pierre Gratier; François Renard (Pure and Applied Geophysics, 2015)

True potato seed research and development in Vietnam - Vu Tuyen Hoang; Pham Xuan Liem; Vu Bich Dan; Ngo Doan Dam; Nguyen Xuan Linh; Nguyen Van Viet; Pham Xuan Tung; Peter Vander Zaag (American Journal of Potato Research, 1988)